Effects of Disaster on Primary Health Care in Low Income Countries - Ray, Kirti; Ghimire, Jagadishwor; BC, Rajendra Kumar (Journal of Nepal Health Research Council, 2019)
Primary health care is considered to be a practical approach to provide basic curative, preventive and promotive health care as an accessible medium for the people particularly in low resource income countries in an affordable way. This paper reviewed that an integrated primary health care system could reduce fundamental vulnerability of disasters; thereafter protect the health facilities and services for providing health programs. Further it focused on the increased uptake on health services to build resilience among individuals of low resource countries having high exposure to disasters. It also provides an idea on the practices adapted for gaining resilience of primary health care of low resource regions like Africa, South and South East Asia which are frequently exposed to disasters. However, this study did not focus on the health governance, pre-hospital disaster management and funding policies which are limited at present in low income countries affected by frequent disasters.Keywords: Disasters; disaster management; low income countries; primary health care; resilience.